Effect of intrinsic and extrinsic foot muscle strengthening exercises on foot parameters and foot dysfunctions in pregnant women: a randomised controlled trial. (22nd March 2019) - Ramachandra, Preetha; Kumar, Pratap; Kamath, Asha; Maiya, Arun G
No abstract available